The effect of local heat therapy on gastric residual volume and abdominal distention in patients with nasogastric tube feeding: A randomized controlled clinical trial - Sadighe Sadeghian; Ali Mohammadpour; Masoumeh Salari (Tehran University of Medical Sciences, 2019)
Background & Aim: Increase in gastric residual volume and abdominal distention are important complications in patients with nasogastric tube feeding. This study aimed to determine the effect of local heat therapy on gastric residual volume and abdominal distention in patients with nasogastric tube feeding. Methods & Materials: In this double-blind clinical trial, 64 patients with nasogastric tube feeding, were selected using the convenience sampling method according to the inclusion criteria and randomly assigned to either the experiment group or control group. For two groups, a hot pack was placed on the anterior abdominal region in two 23-minute sessions, about 1.5 hours after gavage. The temperature of the hot pack was 50°C for the experiment group and it was equal to the ambient temperature for the control group. The levels of patients' abdominal distention and gastric residual volume were measured and compared half an hour before and 1.5 hours after gavage. Data collection tools were consisted of a demographic questionnaire and a data sheet for recording digestive function. Data were analyzed using the SPSS software version 16 through descriptive and inferential statistical tests. The p-value less than 0.05 was considered significant. Results: According to the results, 46.9% of the patients were female and 53.1% were male. The age mean for the experiment and control groups were 12.5±72.5 and 15.3±7.8, respectively. There was no significant difference between the two groups in terms of demographic characteristics and disease-related information. Abdominal distention and gastric residual volume were similar in the two groups before the intervention, but significantly decreased in the experiment group after the intervention (P<0.05). However, there was no significant difference in the control group. Conclusion: Local heat therapy reduces gastric residual volume and abdominal distention in patients with nasogastric tube feeding, and its application is suggested in further research. Clinical trial registry: IRCT2015050822163N1